Redefining the sensitivity of screening mammography: A review - Hollingsworth, Alan B. (The American journal of surgery, 2019)
From its inception, screening mammography has enjoyed a perceived level of sensitivity that is inconsistent with available evidence. The original data that imparted erroneous beliefs about sensitivity were based on a variety of misleading definitions and approaches, such as the inclusion of palpable tumors, using the inverse of interval cancer rates (often tied to an arbitrary 12 month interval), and quoting prevalence screen sensitivity wherein tumors are larger than those found on incidence screens. This review addresses the background for the overestimation of mammographic sensitivity, and how a major adjustment in our thinking is overdue now that multi-modality imaging allows us to determine real time mammographic sensitivity. Although a single value for mammographic sensitivity is disingenuous, given the wide range based on background density, it is important to realize that a sensitivity gap between belief and reality still exists in the early detection of breast cancer using mammography alone, in spite of technologic advances. Failure to recognize this gap diminishes the acceptance of adjunct methods of breast imaging that greatly complement detection rates. •The sensitivity of mammography has been overstated since its inception.•With the introduction of adjunct imaging methods, this error became apparent.•Screening ultrasound adds significantly to cancer detection in dense breasts.•Screening MRI adds significantly to cancer detection in high risk patients.•Benefit of adjunct imaging can also be demonstrated in the general population, but cost-effectiveness becomes a challenge.